Thyrotoxic periodic paralysis associated with Graves' disease: a case series. (10th February 2022) - Ludgate, S; Lin, M; Mayadunne, M; Steen, J; Ho, K W
Abstract : Summary: Thyrotoxic periodic paralysis (TPP) is a rare condition characterised by acute onset hypokalaemia and paralysis which most commonly affects men of Asian descent between the ages of 20 and 40 years ( 1, 2 ). It has been reported in approximately 2% of patients with thyrotoxicosis in China and Japan ( 1, 2, 3 ). Hypokalaemia in TPP results from a massive intracellular shift of potassium induced by the thyroid hormone sensitisation of Na + /K + -ATPase ( 4 ). Treatment of TPP includes prevention of this shift by using beta-blockade, rapid potassium replacement and treatment of the underlying hyperthyroidism. We present two cases of TPP with differing outcomes. In the first case, a 33-year-old Filipino gentleman presented to our emergency department (ED) with a 3-month history of recurrent proximal lower limb weakness. Serum potassium was 2.2 mmol/L (3.3–5.1) and he was given i.v. potassium replacement. Thyroid function tests (TFTs) and thyroid antibodies were consistent with Graves thyrotoxicosis. He was discharged home on carbimazole and remains well controlled on long-term medical therapy. In the second case, a 22-year-old Malaysian gentleman presented to our ED with new-onset bilateral lower limb painless paralysis. Serum potassium was 1.9 mmol/L with TFTs demonstrating Graves thyrotoxicosis. He was treated with i.v. potassium replacement and discharged home on carbimazole and propranolol. He represented to the hospital on two further occasions with TPP and was advised to consider total thyroidectomy given his refractory Graves' disease. These cases highlight the importance of prompt recognition of this rare life-threatening complication of Graves' disease, especially in patients of Asian descent. Learning points: Thyrotoxic periodic paralysis is a rare condition characterised by hypokalaemia and acute painless muscle weakness in the presence of thyrotoxicosis. The signs and symptoms of thyrotoxicosis can be subtle in these patients. It is most commonly seen in Asian males between the ages of 20 and 40 and is most frequently caused by Graves' disease. Prompt recognition is essential as it is a life-threatening condition. Urgent i.v. potassium replacement and beta-blockade with a non-selective beta-blocker are the mainstays of treatment. i.v. potassium replacement should not be given in dextrose as this can potentiate hypokalaemia.